2005
DOI: 10.1021/jf0501342
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Incorporated Wild Solanum Genomes on Potato Properties in Terms of Starch Nanostructure and Glycoalkaloid Content

Abstract: Interspecific somatic hybrids produced by protoplast fusion between two wild Solanum species (S. acaule, acl; S. brevidens, brd) and cultivated potato Solanum tuberosum (tbr) were analyzed in terms of the starch nanometer-range structure and glycoalkaloid (GA) contents. The crystallinity of starch granules, the average size of starch crystallites, and the lamellar distances were obtained from tuber samples using wide-angle and small-angle X-ray scattering methods. These measurements showed that incorporation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(14 citation statements)
references
References 32 publications
0
14
0
Order By: Relevance
“…In somatic hybrids, whose production does not involve meiosis for gamete production, detection of new types of molecules is a rather rare event. Mattheij et al [16] and Väänänen et al [19] reported a similar finding in S. tuberosum -S. circaeifolium and S. tuberosum -S. brevidens somatic hybrids, respectively. It is possible that the new metabolites represent new GAs.…”
mentioning
confidence: 68%
“…In somatic hybrids, whose production does not involve meiosis for gamete production, detection of new types of molecules is a rather rare event. Mattheij et al [16] and Väänänen et al [19] reported a similar finding in S. tuberosum -S. circaeifolium and S. tuberosum -S. brevidens somatic hybrids, respectively. It is possible that the new metabolites represent new GAs.…”
mentioning
confidence: 68%
“…þ as base ion [24]. This alkaloid eluting at 8.4 min showed an aglycone ion at m/z 414.33, corresponding to a solanidane with two O-atoms, and a carbohydrate moiety analogous to that described for dehydrodemissine.…”
mentioning
confidence: 88%
“…The use of wild germplasm in potato breeding is extensive and the transmission of unusual SGAs or high total SGA varies with the species used for trait introgression (Väänänen et al , 2006van Gelder and Scheffer 1991). Various studies have been done to understand the occurrence and inheritance of specific SGAs in wild species and their transmission to cultivated germplasm (Gregory et al 1980(Gregory et al , 1981.…”
Section: Genetic Manipulation Of Sgasmentioning
confidence: 99%